A system of sustainable building construction materials incorporating the raised floor innovation – the Tasik Chini Research Centre experience - Tahir M.M.,; I.M.S. Usman,; Mohd-Nor M.F.I.,; Goh Abdullah N.A.,; Abdul Halim Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Malaysian construction industry sector covers the aspects of the planning, design, conservation, demolition and repairing of various types of buildings and all types of mechanical and civil engineering works as well as other field work involved. It has attracted many researchers and most studies that have been done on the construction industry revolved around the study of technology as a design analysis. However, in reality it is still largely dependant on a conventional system established decades ago. This paper intends to propose a system of sustainable construction materials by redefining the traditional Malay architecture element of the raised floor and its innovation with the Industrialised Building System (IBS). The paper will present experience from Tasik Chini Research Centre of UKM as an alternative solution in providing a more significant and comprehensive construction process, offering fast and efficient system using components or materials that are sustainable. The development in itself incorporated the philosophy of or treading the earth gently, a development aimed at reducing the impact on the environment by lifting buildings from the ground. It complied with UNESCO development guidelines and the Strategic Implementation Action Plan for Tasik Chini's Biosphere Reserves. The development used traditional architectural principles as references and applied the many significant constructs and variables that may influence development in a tropical setting. A raised floor architectural concept was integrated with a structural system, thus providing a diverse range of functions. An IBS systems was implemented with the use of structures, floor panels and modular walls using low thermal mass (low thermal mass) materials, as well as green roofs with green concrete use to prevent heat from sunlight. It proposes a new paradigm in architecture that includes sustainability concern, technological simplicity as well as social aspiration and architectural identity. The system is designed to incorporate many passive design principles and climatic controls that combine with the use of IBS thus making it an efficient and easy-to-install system.